One Health approach for the prevention of open defecation: a panacea for open defecation-driven neglected tropical diseases in sub-Saharan Africa - Orish, Verner N.; Addei, Isaac B.; Adzah, David E.; Oteng, Acheampong G.; Ayaaba, Moses A.; Marinkovic, Aleksandra; Gardellini, Tatiana; Izurieta, Ricardo; Pandit, Rajashree; Okorie, Chuku; Sanyaolu, Adekunle (Frontiers in Tropical Diseases, 2025)
Parasites depend on complex life cycles that involve multiple hosts and different environmental elements. Human and animal feces provide a medium for some of these parasites, especially those responsible for some Neglected Tropical Diseases (NTDs), to be transmitted between their intermediate and definitive hosts. Open defecation has been identified as a menace that contributes significantly to the spread of these parasites. While preventive strategies like the WASH initiatives have shown promising results, improper feces disposal has offset these achievements by contaminating the environment, especially soil, water, and crops. Furthermore, the poor attention to open defecation of animals has allowed these parasites to contaminate and pollute the environment and transmit diseases with relative ease, with no environmental legislation. As a result, certain NTDs-Open defecation driven-NTDS such as Soil-Transmitted Helminthiasis, Schistosomiasis, Taeniasis, Cysticercosis, and Echinococcosis have become increasingly successful in their spread, a situation driven by both human and animal open defecation. This article explores how the practice of open defecation by both humans and animals aids in spreading these NTDs, and it highlights how a One Health integrated approach might provide a lasting solution for these Open defecation driven NTDs in Sub-Saharan Africa.